2017
DOI: 10.1080/20426445.2017.1400756
|View full text |Cite
|
Sign up to set email alerts
|

Binderless boards made of milled coconut husk: an analysis of the technical feasibility and process restraints

Abstract: The possibility of producing binderless panels made of milled coconut husk, a largely available by-product of the coconut oil industry, has been shown in previous researches. Long pressing times and a high risk of blisters have however hindered the industrial implementation of the process. In this study, a more energy-efficient manufacturing process, involving a tailored degassing step, was developed on a laboratory scale and then validated at an industrial size (2 × 1 m 2 ). To achieve mechanical properties c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The manufactured boards from whole coconut husks exhibited characteristics which were similar to, or better than, commercial wood panels. Böger et al [10] investigated the production of binderless panels from milled coconut husk by developing an energy-efficient manufacturing process at laboratory scale. The study found that required moisture content for the successful production of fiberboards using the hot-pressing process was between 10 and 25%.…”
Section: Introductionmentioning
confidence: 99%
“…The manufactured boards from whole coconut husks exhibited characteristics which were similar to, or better than, commercial wood panels. Böger et al [10] investigated the production of binderless panels from milled coconut husk by developing an energy-efficient manufacturing process at laboratory scale. The study found that required moisture content for the successful production of fiberboards using the hot-pressing process was between 10 and 25%.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that though coconut husk is a promising material for production of composite ceilings and other insulation panels [14][15][16][17], it is majorly under-utilized. As of April 29, 2019, it was reported in the Guardian Newspaper that increase in global demand for coconut exceeded 500% in the past five years.…”
Section: Introductionmentioning
confidence: 99%
“…3 Flowchart of product-and-construction-process-stage (A1-A5) for social house made from reinforced concrete frame and hollow block filling Fig. 4 Flowchart product-and-construction-process-stage (A1-A5) for cement-bamboo frame house (Base Builds 2015) Boeger et al (2017), Snijder et al (2005), Keijsers (2006), TenHave et al (2010) and the Philippine Coconut Authority (2012). The husks are typically considered a waste product.…”
Section: Phases A1-a5 For Coconut Board-based Housementioning
confidence: 99%
“…Fig. 5 Flowchart product-and-construction-process-stage (A1-A5) for coconut board-based house to be applied in the Philippines (Boeger et al 2017) 2.2.5 Phase B: use phase of the houses LCAs are more often used in exemplary projects with building-integrated technical systems, not for ordinary building stock (Cabeza et al 2014). Multiple studies for exemplary houses state that energy consumption during the use phase (phase B6) of the house contributes 70-90% to the overall life cycle balance (Ortiz et al 2009;Cabeza et al 2014;Abd Rashid and Yusoff 2015).…”
Section: A1-a5mentioning
confidence: 99%
See 1 more Smart Citation